2022
DOI: 10.3389/fpubh.2022.751615
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics of 5,569 Pediatric Burns in Central China From 2013 to 2019

Abstract: BackgroundPediatric burns of all the ages are prevalent worldwide, posing a severe health risk to children. This study aims to examine pediatric burns' clinical characteristics and epidemiology in central China.MethodsThe pediatric patients of the Burn Research Center, Department of the First People's Hospital of Zhengzhou City from 2013 to 2019 were retrospectively studied and the relevant data were collected from the hospitalized medical records [e.g., demographic, etiology, length of stay (LOS), age, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Numerous studies have investigated the clinical characteristics of children with burns (20)(21)(22)(23)(24)(25)(26)(27). The demographic characteristics and burn history of children with burns were similar to our results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Numerous studies have investigated the clinical characteristics of children with burns (20)(21)(22)(23)(24)(25)(26)(27). The demographic characteristics and burn history of children with burns were similar to our results.…”
Section: Discussionsupporting
confidence: 88%
“…Santos et al (20) reported that burn injuries were found higher among boys and that most burns were due to hot liquid or objects in Portugal. In studies by Han et al (21) conducted in Central China and by Nthumba (24) conducted in sub-Saharan Africa, it was shown that boys had higher burn injuries than girls. A review study indicated that burns were more prevalent among low socioeconomic populations and undeveloped regions (27).…”
Section: Discussionmentioning
confidence: 98%
“…Our nding also revealed that (4.6%) of participants were diabetic patients much different from study conducted in Iran (23.5%) (21).This signi cant gap may be due to the sociocultural and genetic variation of the study subjects. Pre hospital intervention was done for (31.5%) but relatively less than report is found study conducted in bahirdar (35.3%) and Mekele(52.8%) (9,14)which have signi cant impact on the management outcome of burn injury, children who have gotten pre hospital intervention has 0.2 times more chance to discharge without complication((AOR;0.20,95% CL(0.05-0.85),this supported by study in Bangladesh, Ghana and Nigeria (22)(23)(24). This discrepancy might be because of difference in accessibility of rst aid management and community awareness about pre hospital care.…”
Section: Discussionmentioning
confidence: 91%
“…In China, there have been some published studies focusing on the medical cost of burns. In central China, a study reported that the median cost of pediatric burn inpatients was US $1,511 ( 33 ). Another study conducted in Wuhan suggested that the mean cost of pediatric burns was 11,210.76 and 1,630 CNY per % TBSA ( 34 ), which was lower than those in our study.…”
Section: Discussionmentioning
confidence: 99%